Silicon-based double hetero-junction visible blind ultraviolet detector and manufacturing method thereof - GU CHANGZHI; MEI ZENGXIA; GUO YANG; ZHANG TIANCHONG; DU XIAOLONG (2009)
The invention discloses a silicon-based double heterojunction visible-blind UV detector and a manufacturing method thereof. The detector comprises a p-Si substrate, an MgO insulating layer, an n-ZnO-based thin film layer, an n-type ohmic contact electrode and a p-type ohmic contact electrode. The manufacturing method of the detector comprises the following steps: the MgO insulating layer is grown on a clean Si substrate by an epitaxial growth device, and the n-ZnO-based thin film layer is grown on the MgO insulating layer; the n-type ohmic contact electrode is deposited on the n-ZnO-based thin film layer by the well-known photo lithography and the well-known metal thin film deposition method; and the p-type ohmic contact electrode is deposited on the back face of the Si substrate. By the manufacturing method, high-performance visible-blind UV detectors can be manufactured on semiconductor Si substrates which are cheap and have mature integrated process.